Interhemispheric Connectivity in Drug-Naive Benign Childhood Epilepsy With Centrotemporal Spikes. Issue 37 (September 2015) - Wu, Yun; Ji, Gong-Jun; Li, Ke; Jin, Zhen; Liu, Ya-Li; Zeng, Ya-Wei; Fang, Fang; Yong., Li
<x xml:space="preserve">Abstract</x> Abstract Decreased intelligence quotients (IQ) have been consistently reported in drug-naive benign childhood epilepsy with centrotemporal spikes (BECTS). We aimed to identify the neurophysiological basis of IQ deficits by studying interhemispheric and anatomical functional connectivity in BECTS patients. Resting-state functional and structural magnetic resonance images were acquired in 32 children with BECTS and 25 healthy controls. The IQ was estimated using Wechsler Intelligence Scale for Children China-Revised. The functional connectivity between bilateral homotopic voxels was calculated and compared between groups. Homotopic regions showing abnormal functional connectivity in patients were adopted as regions of interest for analysis by diffusion-tensor imaging tractography. The fractional anisotropy, fiber length, and fiber number were compared between groups. Abnormal homotopic connectivities were correlated with IQ in BECTS patients. Compared with control subjects, patients showed decreased IQ, and decreased voxel-mirrored homotopic connectivity (VMHC) in the bilateral frontal lobule and cerebellum. The performance and full scale IQ significantly increased with the VMHC strength of the middle frontal gyrus (MFG) in controls but not in BECTS patients. A significant negative correlation was observed between VMHC in the premotor cortex and disease duration. Microstructural features within white matter tracts connecting functionally abnormal regions did not reveal any differences between groups. This study provides preliminary evidence for the disrupted functional cooperation between hemispheres in children with BECTS. The findings suggest that the hyposynchrony between the bilateral MFG may be involved in the decreased IQ of BECTS patients.